Cotton Candy Machine Explore Its Potential For Fabrication Of Polymer Microfiber For Vascular Tissue Engineering Application - Aziz, Nazatul Shafiqah Abdul (2019)
This work presents the fabrication of scaffold by using freeze extraction method and cotton candy machine for application vascular tissue engineering. The single layer scaffold by cotton candy machine was studied on different polylactic acid (PLA) annealing time for 24 hours, 48 hours and 72 hours in 80°C to analyse the optimize single layer scaffold. The single layer scaffold in different concentrations 3 wt%, 6 wt%, and 9 wt% of poly(L-lactic acid-co-ε-caprolactone) (PLCL) produced by using freeze extraction method was investigated. The combination of boths method were produced to form double and multilayer scaffold. The ideal scaffold was fabricated to form tissue scaffold that similar to the native cardiovascular tissue. The morphological changes in different concentrations PLCL and PLA annealing time were observed via scanning electron microscope (SEM) with porosity varied from 21 % to 32 % for PLA scaffold with different annealing time of PLA and 19 % to 43 % for different concentrations of PLCL. The 72 hours of the PLA annealed time were smaller diameter and smaller pore size. The 9 wt% of concentration PLCL was optimum single scaffold by freeze extraction method due to the largest pore size forms compare to others. The double layer scaffold were shows that, it is suitable to form scaffold compared to the multilayer scaffold due to the formation of gap between layer.